2013
DOI: 10.3892/mmr.2013.1418
|View full text |Cite
|
Sign up to set email alerts
|

Functions of corneal endothelial cells do not change after uptake of superparamagnetic iron oxide nanoparticles

Abstract: To avoid donor tissue shortages, ex vivo cultured human corneal endothelial cell (HCEC) transplantation is a promising therapeutic resource. Superparamagnetic iron oxide nanoparticle (SPION) cell labeling assists HCEC transplantation by attaching the posterior corneal stroma in ex vivo animal models. However, possible functional changes of the HCECs following SPION labeling remain to be determined. In this study, we used SPIONs to label cultured rabbit CECs (RCECs) in order to observe important cell functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…SPIONs are considered to be inert imaging agents without intended pharmacological functions and they are often classified as biocompatible, showing no severe toxicity in vivo. , While Sharifi et al have reported the ability of SPIONs to considerably change gene expression in human adipocytes switching on the obesity and type 2 diabetes associated risk genes, other works have shown no or minimal alteration of gene expression or cellular functions. , This suggests that biological effect of SPIONs is cell type specific, with cells more responsive to oxidative stress probably being more sensitive to SPIONs.…”
Section: Introductionmentioning
confidence: 99%
“…SPIONs are considered to be inert imaging agents without intended pharmacological functions and they are often classified as biocompatible, showing no severe toxicity in vivo. , While Sharifi et al have reported the ability of SPIONs to considerably change gene expression in human adipocytes switching on the obesity and type 2 diabetes associated risk genes, other works have shown no or minimal alteration of gene expression or cellular functions. , This suggests that biological effect of SPIONs is cell type specific, with cells more responsive to oxidative stress probably being more sensitive to SPIONs.…”
Section: Introductionmentioning
confidence: 99%
“…44, 45 These data are consistent with others’ findings, although other nanoparticles may have systemic toxicities. 41, 46 For example, silica and titanium dioxide nanoparticles, of 70 and 35 nm diameters, injected intravenously into pregnant mice were found to cross the placenta and cause pregnancy complications. 47 Functionalization of nanoparticles with polyethylene glycol chains has been found to minimize teratogenic effects below a certain threshold injection dose.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as many therapeutic MENMs are functionalized with a drug of interest, and even if the functionalized MENMs demonstrate good biocompatibility [ 151 ] it is critical that the therapeutic arrives at the correct destination to reduce unwanted interactions. In a study utilizing superparamagnetic iron oxide nanoparticles (SPIONs), no inhibition of rabbit endothelial cell function in vitro was observed [ 152 ]. Additionally, in a separate study, these particles were used to guide bovine corneal endothelial cells to an injured area via an external magnetic force without impacting cell viability or disturbing the cytoskeleton [ 153 ].…”
Section: Toxicity and Utilization Of Metallic Enms In Ophthalmologymentioning
confidence: 99%